Onward Christian soldiers! Christians in the army - Van de Beek, A. (Faculty of Theology, University of the Free State, 2006)
On the topic of Christians in the army, the author compares two traditions in Christian theology, one of which being Eusebius. In this tradition, soldiers are praised as warriors for the sake of God. A recent sermon from the USA and one from nineteenth-century Germany are analysed, compared and positioned within the tradition of Eusebius. The second tradition, characterised as pacifist, was dominant in the early church. Texts of Tertullian and Origen are analysed. It is argued in the third section that war can only be justified within a religious framework. A memorial ceremony in the Netherlands serves as the eye opener. The conclusion is drawn that both traditions dealing with holiness in respect of soldiers in the army exclude each other. This implies that much homework will be required from theologians in order to clarify the Christian theological position.
Keywords: Christian ethics; War; Pacifism